2013
DOI: 10.1111/bjd.12578
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from gene expression profiling of cutaneous T-cell lymphoma

Abstract: Gene expression studies of cutaneous T-cell lymphoma (CTCL) span a decade, yet pathogenesis is poorly understood and diagnosis remains a challenge. This review examines the varied approaches to gene expression analysis of CTCL, with emphasis on cell populations, control selection, and expression data collection. Despite discordant results, several dysregulated genes have been identified across multiple studies including PLS3, KIR3DL2, TWIST1, and STAT4. Here, we provide an overview of the most consistently exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 84 publications
(236 reference statements)
5
45
2
1
Order By: Relevance
“…27,28 PLS3 (Plastin 3) is an actin binding protein, which is also normally not expressed in T cells. 6,29 Our RT-PCR analysis confirms that BLK, POU2AF, TOX, EVA1, and PLS3 are expressed in CTCL lesional skin biopsies (Fig. 2).…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…27,28 PLS3 (Plastin 3) is an actin binding protein, which is also normally not expressed in T cells. 6,29 Our RT-PCR analysis confirms that BLK, POU2AF, TOX, EVA1, and PLS3 are expressed in CTCL lesional skin biopsies (Fig. 2).…”
Section: Resultssupporting
confidence: 70%
“…27,51 In addition, recent translational experimental work revealed that TOX expression, which is usually silenced in mature T cells, can be used as a robust prognostic and diagnostic marker for MF and SS, 52,53 while PLS3 actin binding protein, which is usually not expressed in T cells is consistently expressed in CTCL. 6,29,54,55 A growing body of literature documents that ectopic expression of these genes in CTCL is not a mere indication of deregulated cellular processes, but an important mechanism of tumorigenesis and cancer progression. Our study confirms that select thymocyte development genes (e.g., EVA1 and TOX), B cell-specific genes (POU2AF and BLK) and PLS3 are expressed in CTCL lesional skin and in patient-derived cell lines.…”
Section: E970025-4 Volume 3 Issue 11 Oncoimmunologymentioning
confidence: 99%
See 1 more Smart Citation
“…Malignant CTCL cells were identified both by CD4 positivity and TOX expression. [49][50][51] Indeed, TOX is only expressed by ;60% of CD4 1 T cells in skin biopsies from patients with confirmed CTCL diagnosis, and it is not expressed by NS or skin from AD ( Figure 1B-C), a benign inflammatory skin condition that presents some clinical and histologic features common to CTCL 50,52 and harbors a large number of infiltrating CD4…”
Section: Il-13 In the Pathogenesis Of Ctcl 2799mentioning
confidence: 99%
“…Although the etiology of CTCL is not yet clear, accumulating evidence indicates that defects in apoptosis and cell cycle control are critical in disease pathogenesis. [5][6][7][8] However, the molecular events leading to these abnormalities have not been well understood. By transcriptome analysis, we have recently demonstrated that the transcript levels of thymocyte selection-associated high-mobility group (HMG) box gene (TOX) are abnormally increased in early-stage MF skin biopsy specimens but not in the biopsy specimens of benign inflammatory dermatoses (BID) or normal skin.…”
Section: Cd45romentioning
confidence: 99%